2017
DOI: 10.1007/s11060-017-2429-5
|View full text |Cite
|
Sign up to set email alerts
|

Flow arrest intra-arterial delivery of small TAT-decorated and neutral micelles to gliomas

Abstract: The cell-penetrating trans-activator of transcription (TAT) is a cationic peptide derived from human immunodeficiency virus-1. It has been used to facilitate macromolecule delivery to various cell types. This cationic peptide is capable of crossing the blood-brain barrier and therefore might be useful for enhancing the delivery of drugs that target brain tumors. Here we test the efficiency with which relatively small (20 nm) micelles can be delivered by an intra-arterial route specifically to gliomas. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, at low receptor levels (or in the absence of receptors), there was a decrease in targeting in the high velocity and high diffusion range. These results are consistent with a recent work of Nguyen et al [33], who have shown that nanoparticle uptake in a glioma is promoted under flowarrest condition (hyperfusion). Based on these results, the gain from the active targeting might be relatively high in the higher interstitial fluid velocity or diffusion ranges.…”
Section: Effects Of Particle Size Fluid Velocity and Particle Diffusionsupporting
confidence: 93%
“…However, at low receptor levels (or in the absence of receptors), there was a decrease in targeting in the high velocity and high diffusion range. These results are consistent with a recent work of Nguyen et al [33], who have shown that nanoparticle uptake in a glioma is promoted under flowarrest condition (hyperfusion). Based on these results, the gain from the active targeting might be relatively high in the higher interstitial fluid velocity or diffusion ranges.…”
Section: Effects Of Particle Size Fluid Velocity and Particle Diffusionsupporting
confidence: 93%
“…When combined with BBB disruption induced by focused ultrasound, intra-arterial liposome injection increases their deposition into tumor tissue of C6 tumor-bearing rats (158). Similarly, application of cationizable lipid micelles (163) with cationic short peptides such as the cell-penetrating trans-activator of transcription (TAT) was shown to increase the uptake of micelles (165) and can be used for selective drug delivery to gliomas. The translocation efficiency of nanoparticles is not only determined by surface charge.…”
Section: Bbb/btb Disruptionmentioning
confidence: 99%
“…The treatment effect was reported to last for more than 4 h (175). Furthermore, TCH is sufficient to enhance early regional deposition of nanoparticles such as micelles (163)(164)(165) and liposomes (158)(159)(160)(161)(162) into tumor tissues. This provides a novel approach for targeted intra-arterial tumor therapy ( Table 3).…”
Section: Tchmentioning
confidence: 99%
“…Plain and CCR2-targeting micelles were prepared as follows: mPEG-DSPE/NHS-PEG-DSPE/DiD (98/2/0.5) were dissolved in chloroform and mixed with the CCR2 antagonist dissolved in methanol. 14,18,19 The small molecule antagonist CCR2 was loaded into the lipid micelles at 1:22 molar ratio, which corresponds to a loading of 4.5% w/w. The solvent was removed by rotary evaporation to yield a lipid film.…”
Section: Micelle Synthesismentioning
confidence: 99%